2016
DOI: 10.3390/ijms17071022
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Underlying Activation of α1-Adrenergic Receptor-Induced Trafficking of AQP5 in Rat Parotid Acinar Cells under Isotonic or Hypotonic Conditions

Abstract: Defective cellular trafficking of aquaporin-5 (AQP5) to the apical plasma membrane (APM) in salivary glands is associated with the loss of salivary fluid secretion. To examine mechanisms of α1-adrenoceptor (AR)-induced trafficking of AQP5, immunoconfocal microscopy and Western blot analysis were used to analyze AQP5 localization in parotid tissues stimulated with phenylephrine under different osmolality. Phenylephrine-induced trafficking of AQP5 to the APM and lateral plasma membrane (LPM) was mediated via the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 66 publications
0
5
1
Order By: Relevance
“…c). Conversely, several studies have demonstrated that the increase in [Ca 2+ ] i is associated with AQP5 translocation into the acinar luminal membrane, and impaired AQP5 translocation is induced by diabetes . Thus, the diminished increase in [Ca 2+ ] i in KK‐A y mice found in the present study may affect AQP5 translocation, which, in turn, may result in salivary dysfunction.…”
Section: Discussioncontrasting
confidence: 53%
“…c). Conversely, several studies have demonstrated that the increase in [Ca 2+ ] i is associated with AQP5 translocation into the acinar luminal membrane, and impaired AQP5 translocation is induced by diabetes . Thus, the diminished increase in [Ca 2+ ] i in KK‐A y mice found in the present study may affect AQP5 translocation, which, in turn, may result in salivary dysfunction.…”
Section: Discussioncontrasting
confidence: 53%
“…Collectively, the present study revealed that oral stimulation with capsaicin generates pungent taste (irritating) sensation which leads to increase in beta wave in EEG suggesting attention increase, and it reflexively causes increases in salivary flow and SIgA secretion with simultaneous elevation of sympathetic activities. Since acinar cells of salivary glands express adrenergic receptors as well as cholinergic receptors, sympathetic activation by capsaicin might result in secretions of fluid, SIgA and α-amylase via α- and β-adrenergic receptors 16, 34, 35, 36. For elucidation of precise mechanisms underlying these effects and relationships between salivary changes and neuronal activities, further molecular and physiological studies will be required.…”
Section: Discussionmentioning
confidence: 99%
“…abolished by the TRP channel blocker ruthenium red [108], suggesting a requirement for TRP channel activity in the hypotonicity-induced relocalisation of AQP5, similarly to AQP1 in HEK293 cells [37] and AQP4 in primary human astrocytes [6].…”
Section: Aqp5mentioning
confidence: 99%